PENGARUH KUALITAS PRODUK, LOKASI, DAN WORD OF MOUTH TERHADAP KEPUASAN KONSUMEN DI WARUNG GOCENG KELAPA DUA - Farhan Yusmana; Sinthon L Siahaan (LPPM Universitas Asa Indonesia, 2023)
This study aims to determine the influence of location, word-ofmouth, and product quality on customer satisfaction at Warung Goceng Kelapa Dua. This study used 130 respondents, of which 30 respondents were for validity and reliability tests, and 100 respondents for data processing. The population in this study is customers who come to the goceng stall. The research method used is quantitative descriptive and the analysis method uses multiple linear regression and the sample in this study uses incidental sampling techniques. The results of this study show that partially product quality affects consumer satisfaction, location affects consumer satisfaction, and word of mouth affects consumer satisfaction. While simultaneously product quality, location, and word of mouth affect together on consumer satisfaction.